Development of Mast Cell and Eosinophil Hyperplasia and HLH/MAS-Like Disease in NSG-SGM3 Mice Receiving Human CD34+ Hematopoietic Stem Cells or Patient-Derived Leukemia Xenografts. Issue 1 (January 2021) - Janke, Laura J.; Imai, Denise M.; Tillman, Heather; Doty, Rosalinda; Hoenerhoff, Mark J.; Xu, Jiajie J.; Freeman, Zachary T.; Allen, Portia; Fowlkes, Natalie Wall; Iacobucci, Ilaria; Dickerson, Kirsten; Mullighan, Charles G.; et al.
Immunocompromised mouse strains expressing human transgenes are being increasingly used in biomedical research. The genetic modifications in these mice cause various cellular responses, resulting in histologic features unique to each strain. The NSG-SGM3 mouse strain is similar to the commonly used NSG (NOD scid gamma) strain but expresses human transgenes encoding stem cell factor (also known as KIT ligand), granulocyte-macrophage colony-stimulating factor, and interleukin 3. This report describes 3 histopathologic features seen in these mice when they are unmanipulated or after transplantation with human CD34+ hematopoietic stem cells (HSCs), virally transduced hCD34+ HSCs, or a leukemia patient-derived xenograft. The first feature is mast cell hyperplasia: unmanipulated, naïve mice develop periductular pancreatic aggregates of murine mast cells, whereas mice given the aforementioned human cells develop a proliferative infiltrative interstitial pancreatic mast cell hyperplasia but with human mast cells. The second feature is the predisposition of NSG-SGM3 mice given these human cells to develop eosinophil hyperplasia. The third feature, secondary hemophagocytic lymphohistiocytosis/macrophage activation syndrome (HLH/MAS)–like disease, is the most pronounced in both its clinical and histopathologic presentations. As part of this disease, a small number of mice also have histiocytic infiltration of the brain and spinal cord with subsequent neurologic or vestibular signs. The presence of any of these features can confound accurate histopathologic interpretation; therefore, it is important to recognize them as strain characteristics and to differentiate them from what may be experimentally induced in the model being studied.